2021
DOI: 10.1002/pol.20210683
|View full text |Cite|
|
Sign up to set email alerts
|

Spirulina‐based composites for 3D‐printing

Abstract: With material consumption increasing, the need for biodegradable materials derived from renewable resources becomes urgent, particularly in the popular field of 3D-printing. Processed natural fibers have been used as fillers for 3D-printing filaments and slurries, yet reports of utilizing pure biomass to 3D-print structures that reach mechanical properties comparable to synthetic plastics are scarce. Here, we develop and characterize slurries for extrusion-based 3D-printing comprised of unprocessed spirulina a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 78 publications
0
17
0
Order By: Relevance
“…The weakening mechanical performance of the biocomposites is the result of distinct hydration products instead of the structural defects alone. Chlorella and spirulina both have a high concentration of carbohydrates ranging from 13.6 to 54.4 wt % depending on strains and growth conditions, and for both, more than 50% of the carbohydrates have glucose monomers. , In alkaline conditions in cement pastes, glucose degrades into acidic forms such as parasaccharinic acid or glycolic acid, as demonstrated by Yang and Montgomery . Therefore, we reasonably anticipate the acidification of glucose-based carbohydrates in both cases of chlorella and spirulina when mixed with the cement paste.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…The weakening mechanical performance of the biocomposites is the result of distinct hydration products instead of the structural defects alone. Chlorella and spirulina both have a high concentration of carbohydrates ranging from 13.6 to 54.4 wt % depending on strains and growth conditions, and for both, more than 50% of the carbohydrates have glucose monomers. , In alkaline conditions in cement pastes, glucose degrades into acidic forms such as parasaccharinic acid or glycolic acid, as demonstrated by Yang and Montgomery . Therefore, we reasonably anticipate the acidification of glucose-based carbohydrates in both cases of chlorella and spirulina when mixed with the cement paste.…”
Section: Resultsmentioning
confidence: 56%
“…Finally, to explain the different aging behavior between chlorella and spirulina and the higher strength evolution in spirulina composites, we note the different carbohydrate content in the two types of biomatter. We analyzed the carbohydrate content of our biomatters via high performance liquid chromatography (HPLC) (results shown in Figure S5 for chlorella and prior work from Fredricks et al 40 for spirulina) and found that chlorella contains 21.7 wt % carbohydrates, 10.8 wt % of which are glucose-based, while spirulina has 14 wt % carbohydrates, 6.1 wt % of which are glucose-based. This result supports the more significant suppressing effect when chlorella is introduced in cement as compared to spirulina.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 23,56 ] Specifically, the layered conformation and terminal oxygen planes in the tetrahedral structure of montmorillonite (MMT), our nanoclay of choice, would allow enhanced surface interactions and hydrogen bonding with the protein‐ and carbohydrate‐based spirulina matrix. [ 30 ] We note that sonication of the nanoclay and spirulina in water are necessary to promote filler dispersion and enhance interactions by dissociating the cells. Indeed, upon freeze‐drying and hot pressing the nanocomposite bioplastics, we observe that a 5 wt.% nanoclay concentration leads to an improvement of the average flexural strength from 35.1 ± 4.5 to 57.2 ± 7.4 MPa (63% increase), a increase in work to fracture from 0.15 ± 0.03 to 0.29 ± 0.06 MJ m −3 (93% increase), and an increase in stiffness from 3.9 ± 0.7 to 5.3 ± 0.3 GPa (36% increase) over sonicated and freeze‐dried spirulina without the nanoclay (Figure 4f, solid blue line).…”
Section: Resultsmentioning
confidence: 99%
“…Fredricks et al. [ 30 ] demonstrated that unmodified spirulina cells can also be used in additive manufacturing to create inks for direct ink writing. The printed structures had mechanical properties and micromorphologies dependent on the drying method.…”
Section: Introductionmentioning
confidence: 99%